Blood cellular elements and serum proteins in Desert sheep in the Sudan - Hassan, Y.M.; Abdel-Wahab, M.F. (1967)
The blood cellular elements of thirty desert sheep are reported. Values obtained are in agreement with those previously published in other countries with a slight insignificant increase or decrease. Determination of the serum total and differential proteins gave an average value of 6.93 + 0.465 g . This value is more or less close to that found by other authors for serum protein in sheep i.e. 6.69 + 0.23 g. Sedimentation rate values are found to be 1.35 + 1.60. This high deviation was due to the great difference between maximum and minimum values.